ILWIS GIS for Monitoring Landscapes in Tundra Ecosystems: Yamal Peninsula, Russia - Polina Lemenkova; Bruce C. Forbes; Timo Kumpula (Zenodo, 2012)
The paper focuses on the monitoring changes in Russian tundra landscapes and distribution of various land cover types in Yamal Peninsula, Russia, during the past two decades. Specific climate and environmental settings of the study area facilitate seasonal flooding, active erosion processing, permafrost distribution and local landslide formation. Technically, the research has been performed using ILWIS GIS applied for satellite images comparative analysis using GIS supervised classification methods. P. Lemenkova, B. Forbes, and T. Kumpula. "ILWIS GIS for Monitoring Landscapes in Tundra Ecosystems: Yamal Peninsula, Russia". In: Remote Sensing and Global Surveillance. 3rd Inter- national Geosciences Student Conference (Association of Geophysicists and Environmentalists of Serbia (AGES), May 29–31, 2012). Serbia, Belgrade, 2012. isbn: 978-86-913953-5-3. doi:10.6084/m9.figshare.7434236.v1.